Advancing culturally relevant pedagogy in college chemistry - Cooper Destinee J.; Voigt Matthew (Chemistry Teacher International)
There is increasing emphasis on incorporating complex global challenges such as sustainable development and environmental justice in college chemistry instruction. Addressing these issues requires a community of engaged citizens who are empowered to enact change in their communities and value diverse perspectives. Culturally relevant pedagogy (CRP) is a framework that may support college chemistry faculty in integrating these social justice aims while also advancing equity within their own classrooms. However, college chemistry instructors’ knowledge and implementation of CRP remains understudied. This research explores how college chemistry instructors (n = 6) from different institutions across the United States describe and operationalize CRP. Thematic analysis of semi-structured interviews indicates that the instructors in this study are flexible in their teaching approach, cultivate a classroom community of collaboration and belonging, and affirm that all students can be successful in chemistry. These practices are foundational elements of CRP, but they must also be coupled with knowledge of students’ cultural backgrounds and awareness of sociopolitical issues that impact students. A framework that considers the context of college chemistry is proposed to support instructors’ adoption of all of the tenets of CRP. Future work will further develop and examine the use of our framework for chemistry faculty development.